Samir Rakshiter chotogalpe shishushramik: Samajer Andhakar Adhyay/ সমীর রক্ষিতের ছোটোগল্পে শিশু শ্রমিক : সমাজের অন্ধকার অধ্যায় (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2024)
Every writer has a responsibility towards society. Samir Rakshit is no exception. He has seen our society from various perspectives. In order to collect a treasury of emotions in literature, he delved deep into the heart of society. As a result, he portrayed the struggles of people from different walks of life in his writings. He did not even neglect the everyday struggle of the children behind the veil of civilized society, who are known as child labourers. In his stories, he has included a significant portion of these children's tales of struggle, intending to present them to the readers and society. he has shown how day by day, due to economic instability, talented children are being lost from this society. In order to grasp the current state of affairs in society, they are resorting to labour in their adolescence to sustain their livelihood in unfamiliar territories. financial stability rather than academic success has now become the benchmark of social recognition. girls like ‘futi’ are constantly fighting to survive, questioning our civilized society every day. So, he has requested everyone to stand by these children, in order to bring back their lost childhood and eradicate child labour.
Keywords: Samir Rakshit; Short Stories; society; child labour; survive